Yahoo Answers: Answers and Comments for MATH POLYNOMIALS? [Mathematics]
Copyright © Yahoo! Inc. All rights reserved.
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
From mikaela
enUS
Thu, 18 Jun 2015 04:54:44 +0000
3
Yahoo Answers: Answers and Comments for MATH POLYNOMIALS? [Mathematics]
292
38
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
https://s.yimg.com/zz/combo?images/emaillogous.png

From Melvyn: im confused too
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
Thu, 18 Jun 2015 05:00:36 +0000
im confused too

From sepia: 1).
(x + 3)(x  1)(x + 2)
= (x + 3)(x^2 + x ...
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
Thu, 18 Jun 2015 05:16:29 +0000
1).
(x + 3)(x  1)(x + 2)
= (x + 3)(x^2 + x  2)
= x(x^2 + x  2) + 3(x^2 + x  2)
= x^3 + x^2  2x + 3x^2 + 3x  6
= x^3 + 4x^2 + x  6
2).
(x^4 + 3x^2  1)(4x^3 + x^2  x + 3)
= x^4 (4x^3 + x^2  x + 3) + 3x^2 (4x^3 + x^2  x + 3)  (4x^3 + x^2  x + 3)
= 4x^7 + x^6  x^5 + 3x^4 + 12x^5 + 3x^4  3x^3 + 9x^2  4x^3  x^2 + x  3
= 4x^7 + x^6 + 11x^5 + 6x^4  7x^3 + 8x^2  3

From cidyah: 1.
(x+3)(x1) = x^2x+3x3 = x^2+2x3
(x^2+2x...
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
Thu, 18 Jun 2015 05:08:15 +0000
1.
(x+3)(x1) = x^2x+3x3 = x^2+2x3
(x^2+2x3)(x+2) = x^3+2x^23x+2x^2+4x6
(x+3)(x1)(x+2) = x^3+4x^2+x6
2.
(x^4+3x^21)(4x^3+x^2x+3)
= 4x^7+x^6x^5+3x^4
+ 12x^5+3x^43x^3+9x^2
4x^3x^2+x3
= 4x^7+x^6+11x^5+6x^47x^3+8x^2+x3

From mizoo: 1. (x + 3)(x  1)(x + 2)
first working on (x...
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
Thu, 18 Jun 2015 05:05:35 +0000
1. (x + 3)(x  1)(x + 2)
first working on (x + 3)(x  1) we have :
= [x * (x  1) + 3 * (x  1)] * (x + 2)
= (x^2  x + 3x  3) * (x + 2)
Add like terms :
= (x^2 + 2x  3) * (x + 2)
= x^2 * (x + 2) + 2x * (x + 2)  3 * (x + 2)
= x^3 + 2x^2 + 2x^2 + 4x  3x  6
= x^3 + 4x^2 + x  6
Here you can find some great examples http://www.mathsisfun.com/algebra/polynomialsmultiplying.html

From Thomas: (x+3)(x1)(x+2) start by multiplying the firs...
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
https://answers.yahoo.com/question/index?qid=20150618045444AASjmQs
Thu, 18 Jun 2015 05:01:00 +0000
(x+3)(x1)(x+2) start by multiplying the first two parenthetical statements
(x+3)(x1) which while you are multiplying is
x*x+1*x+3*x+3*1 which is just x^2+3xx3 grouping like terms leaves
(x^2+2x3) which still needs to by multiplied by (x+2) which is:
x^2*x+2x*x3*x+2*x^2+2*2x+2*3 which is
x^3+2x^23x+2x^2+4x6 grouping like terms...
x^3+4x62+x6